Multiplex immunofluorescence microscopy assays for pharmacodynamic assessment of MET tyrosine kinase activation in the plasma membrane and nucleus - Tony Navas; Apurva K. Srivastava; Scott M. Lawrence; Melinda G. Hollingshead; Sergio Y. Alcoser; Sarah B. Miller; Robert J. Kinders; Donald P. Bottaro; W. Marston Linehan; Shivaani Kummar; James H. Doroshow; Ralph E. Parchment (PLoS ONE, 2026)
The HGF/SF (hepatocyte growth factor/scatter factor) receptor tyrosine kinase MET is overexpressed and/or activated in many tumors, providing therapeutic targets for antibody-drug conjugates and tyrosine kinase inhibitors. Reliable measurement of activated MET is fundamental for pharmacodynamic assessment of MET-targeted therapies and for expanded and proper use of such therapies in patients with tumors driven by activated MET with or without associated MET amplification or known activating mutations. To address the paucity of tools for directly measuring MET activation in tumor cells within patient biopsy specimens, we developed a robust, quantitative immunofluorescence microscopy assay to measure levels of pY 1235 MET and total MET in in vitro , in vivo , and patient tumor specimens. We validated this assay through assessment of MET inhibitor–treated preclinical models, peptide blocking experiments to demonstrate specificity, and concordance with corresponding measurements from the same specimens using a previously validated sandwich immunoassay of tumor lysates. Given the importance of plasma membrane-associated MET in initiating its canonical signaling cascades, as well as the demonstrated non-canonical signaling from nuclear localized MET in different tumor cell types and in response to various environmental stimuli, we developed assay capability to measure levels of pY 1235 MET and total MET within the plasma membrane or nucleus; these assays enable future explorations of the biological and clinical relevance of MET subcellular localization patterns. Finally, using tissue microarrays of over 50 resected tumor specimens from patients with colorectal carcinoma or non-small cell lung cancer, we demonstrated that tumor levels of pY 1235 MET do not always track total MET expression, suggesting that measurement of activated MET in tumor could hold potential as an independent biomarker to identify additional patients who might benefit from MET-directed targeted therapy—beyond those with tumor MET amplification, MET overexpression, or established MET-activating mutations.